Enhancing the accumulation of linoleic acid and α-linolenic acid through the pre-harvest ethylene treatment in Camellia oleifera - Li, Hongbo; Ma, Xiaoling; Wang, Weiqi; Zhang, Jiaxi; Liu, Yuanzhe; Yuan, Deyi (Frontiers in Plant Science, 2023)
Camellia oleifera Abel. (C. oleifera) is an important woody edible oil tree species in China. The quality of C. oleifera oil (tea oil) is mainly determined by the contents of linoleic acid (LA) and α-linolenic acid (ALA). However, how to increase the contents of LA and ALA in tea oil and the corresponding regulating mechanism have not been clarified. In the present study, we found that the LA and ALA contents in C. oleifera seeds were significant positively associated with the concentrations of ethephon and were decreased by ethylene inhibitor treatment. Furthermore, 1.5 g L-1 ethephon could receive an optimal LA and ALA contents without adverse effects to the growth of ‘Huashuo’ trees in this study. The ethephon treatment also increased the contents of 1-aminocyclopropane-1-carboxylic acid (ACC), sucrose, soluble sugar and reducing sugar contents in seeds. Transcriptome analysis further suggested that exogenous ethephon application enhanced the accumulation of LA and ALA via regulating genes involved in LA and ALA metabolism, plant hormone signal transduction pathways, and starch and sucrose metabolism. Our findings confirm the role of ethylene in LA and ALA regulation and provide new insights into the potential utilization of ethylene as a LA and ALA inducer in C. oleifera cultivation.